Potential impact of metabolic syndrome on cognitive function in US firefighters - Seo, Myong-Won; Gann, Joshua; Lee, Jung-Min; Heffernan, Kevin S.; Kim, Joon Young; Jung, Hyun Chul (Frontiers in Public Health, 2023)
Objectives: Among US firefighters, sudden cardiac arrest and psychological stress (i.e., PTSD) are the leading cause of on-duty death. Metabolic syndrome (MetSyn) may influence both cardiometabolic and cognitive health. Here, we examined differences in cardiometabolic disease risk factors, cognitive function, and physical fitness in US firefighters with vs. without MetSyn. Materials and methods: One hundred fourteen male firefighters, aged 20 to 60 years, participated in the study. US firefighters with MetSyn vs. non-MetSyn were divided by AHA/NHLBI criteria. Of them, we performed a paired-match analysis with respect to the age and BMI of firefighters with (n=18) vs. without MetSyn (n=18). The cardiometabolic disease risk factors included blood pressure, fasting glucose, blood lipid profiles (HDL-C, triglyceride (TG), and surrogate markers of insulin resistance (TG/HDL-C, TG glucose index [TyG]). The cognitive test included a psychomotor vigilance task as a measure of reaction time and a delayed-match-to-sample task (DMS) as a measure of memory, using the computer-based Psychological Experiment Building Language Version 2.0 program. The differences between MetSyn and non-MetSyn groups in US firefighters were analyzed using an independent t-test adjusted for age and BMI. In addition, Spearman correlation and stepwise multiple regression were conducted. Results: US firefighters with MetSyn exhibited severe insulin resistance estimated by TG/HDL-C and TyG (Cohen’s d > 0.8, all p < 0.01) compared with their age- and BMI-matched counterparts without MetSyn. In addition, US firefighters with MetSyn exhibited higher DMS total time and reaction time compared with non-MetSyn (Cohen’s d > 0.8, all p < 0.01). In stepwise linear regression, HDL-C predicted DMS total time (β = − 0.440, R2 = 0.194, p < 0.05), and TyG (β = 0.432, R2 = 0.186, p < 0.05) predicted DMS reaction time. Conclusions: US firefighters with vs. without MetSyn were predisposed to metabolic risk factors, surrogate markers of insulin resistance, and cognitive function, even when matched for age and BMI, and there was a negative association between metabolic characteristics and cognitive function in US firefighters. The findings of this study suggest that the prevention of MetSyn may be beneficial to supporting firefighters’ safety and occupational performance.